Imperialism and Sikh migration : the Komagata Maru incident - Roy, Anjali Gera (Routledge studies in South Asian history, 2018)
"In the Punjab, Pakistan, a culture of migration and mobility already emerged in the nineteenth century. Imperial policies produced a category of hypermobile Sikhs, who left their villages in Punjab to seek their fortunes in South East Asia, Australia, America and Canada. The practices of the British Indian government and the Canada government offer telling instances of the exercise of governmentality through which both old imperialism and the new Empire assert their sovereignty. This book focuses on the Komagata Maru episode of 1914: This Japanese ship was chartered by Gurdit Singh, a prosperous Sikh businessman from Malaya. It carried 376 passengers from Punjab and was not permitted to land in Vancouver on grounds of a stipulation about a continuous journey from the port of departure and forced to return to Kolkata where the passengers were fired at, imprisoned or kept undifer surveillance. The author isolates juridical procedures, tactics and apparatus of security through which the British Empire exercised power on imperial subjects by investigating the significance of this incident to colonial and postcolonial migration. Juxtaposing public archives including newspapers, official documents and reports against private archives and interviews of descendants the book analyses the legalities and machineries of surveillance that regulate the movements of people in the old and new Empire. Addressing contemporary discourse on neo-imperialism and resistance, migration, diaspora, multiculturalism and citizenship, this book will be of interest to scholars in the field of diaspora studies, post colonialism, minority studies, migration studies, multiculturalism and Sikh /Punjab and South Asian studies."--Provided by publisher